Effect of Dietary Protein Levels on Growth Performance and Body Composition of Monosex Nile Tilapia, Oreochromis niloticus L. Reared in Fertilized Tanks - Bahnasawy, Mohamed H. (Pakistan Journal of Nutrition, 2009)
Juvenile monosex Nile tilapia (Oreochromis niloticus) were fed four dietary protein levels (17%, 25%, 30% and 35%) to investigate their effects on growth performance, carcass composition and survival rate. The experiment was carried out in concrete tanks (2.9m x 1.4m x 1m), stocking each tank with 160 fish (50 fish/m3). The diets were offered to the fish (2.5±0.1g average initial weight ) at a level of 3% of body weight, six days a week for 180 days. In addition to the experimental diet, inorganic fertilizer was added to each tank at a rate of 6.8 mg/l of premix superphosphate and urea. The results showed that a significant effects of dietary protein on growth performance of the reared fish. Weight gain and specific growth rate increased significantly with increasing dietary protein levels between 17% and 30%. but, 35% crude protein showed insignificant increase in growth parameters. The protein efficiency ratio was inversely correlated with dietary protein levels. The protein content of the fish muscle increased with increasing dietary protein level while the lipid content decreased. The diet had no significant effect on survival rate of the fish. From the present results, diet containing 30% crude protein is considered optimal for growth of monosex Nile tilapia, under the present experimental conditions and it is recommended for feeding monosex tilapia juveniles.